2019
DOI: 10.1111/ppc.12367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors, and patterns of mechanical restraint use for inpatients with dual diagnosis

Abstract: Prevalence, predictors and patterns of mechanical restraint use for inpatients with dual diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…One study reported that males with SCH and comorbid substance abuse were hospitalized more often, and more often subjected to mechanical restraint. 31 Our results concur with many studies that have demonstrated an association between obstetric trauma and SCH, while this association has been less consistently observed for BD. [32][33][34] "Obstetric trauma" encompasses a wide range of birth complications; in the present study patients and/or their caregivers reported hypoxia during birth, premature birth, preeclampsia, and other complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One study reported that males with SCH and comorbid substance abuse were hospitalized more often, and more often subjected to mechanical restraint. 31 Our results concur with many studies that have demonstrated an association between obstetric trauma and SCH, while this association has been less consistently observed for BD. [32][33][34] "Obstetric trauma" encompasses a wide range of birth complications; in the present study patients and/or their caregivers reported hypoxia during birth, premature birth, preeclampsia, and other complications.…”
Section: Discussionsupporting
confidence: 92%
“…One study reported that males with SCH and comorbid substance abuse were hospitalized more often, and more often subjected to mechanical restraint. 31 …”
Section: Discussionmentioning
confidence: 99%
“…They pointed out that, in all groups, the leading cause for MR was danger, vandalism, or assault, hence supporting the view that aggressive behaviors play a significant role in the causative pathway for it. These findings were substantially confirmed by Lykke et al [24], who found that psychostimulant use was significantly associated with violent and aggressive behaviors and, therefore, with a higher MR risk.…”
supporting
confidence: 74%
“…2016; Lykke et al . 2020) and the mean age was around 40 years old (Guzman‐Parra et al . 2020; Jury et al .…”
Section: Discussionmentioning
confidence: 99%
“…2015; Lykke et al . 2020). Furthermore, the most frequent diagnosis was schizophrenia (Guzman‐Parra et al .…”
Section: Discussionmentioning
confidence: 99%